Phylogenetic analysis of Sec7-domain-containing Arf nucleotide exchangers. - Cox, R.; Mason-Gamer, R.J.; Jackson, C.L.; Segev, N. (Molecular Biology of the Cell, 2004)
The eukaryotic family of ADP-ribosylation factor (Arf) GTPases plays a key role in the regulation of protein trafficking, and guanine-nucleotide exchange is crucial for Arf function. Exchange is stimulated by members of another family of proteins characterized by a 200-amino acid Sec7 domain, which alone is sufficient to catalyze exchange on Arf. Here, we analyzed the phylogeny of Sec7-domain-containing proteins in seven model organisms, representing fungi, plants, and animals. The phylogenetic tree has seven main groups, of which two include members from all seven model systems. Three groups are specific for animals, whereas two are specific for fungi. Based on this grouping, we propose a phylogenetically consistent set of names for members of the Sec7-domain family. Each group, except for one, contains proteins with known Arf exchange activity, implying that all members of this family have this activity. Contrary to the current convention, the sensitivity of Arf exchange activity to the inhibitor brefeldin A probably cannot be predicted by group membership. Multiple alignment reveals group-specific domains outside the Sec7 domain and a set of highly conserved amino acids within it. Determination of the importance of these conserved elements in Arf exchange activity and other cellular functions is now possible.